Hepatocyte fatty acid desaturation and polyunsaturated fatty acid composition of liver in salmonids: Effects of dietary vegetable oil - Tocher, Douglas R; Bell, J Gordon; MacGlaughlin, Philip; McGhee, Fiona; Dick, James R (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2001)
The desaturation and elongation of [1-14C]18:3n-3 was investigated in hepatocytes from different populations and three different species of salmonids indigenous to Scotland, brown trout, Atlantic salmon and Arctic charr. Two groups of fish were sampled, before and after they were fed two experimental diets, a control diet containing fish oil and a diet containing vegetable oil (a 1:1 blend of linseed oil and rapeseed oil) for 12 weeks. At each sampling time, fatty acyl desaturation and elongation activity was determined in isolated hepatocytes and samples of liver were also collected for lipid compositional analysis. At the initiation of the dietary trial, the liver polar lipid fatty acid compositions of salmon and brown trout were very similar to each other, and the two charr populations were similar to each other having lower total n-3 polyunsaturated fatty acids (PUFA) and 22:6n-3, but higher 20:5n-3 than the other salmonids. Initially, hepatocyte desaturation activity varied with the highest activity in brown trout followed by salmon then charr. Production of 20:5n-3 was particularly high in brown trout. Desaturation of [1-14C]18:3n-3 was significantly greater in all fish fed the diet containing vegetable oil compared to fish fed the diet containing fish oil. The increase in activity was less in brown trout compared to the other groups of fish. Feeding the vegetable oil diet increased the levels of 18:2n-6, 20:3n-6, total n-6PUFA, 18:3n-3, 18:4n-3, 20:3n-3 and 20:4n-3, and decreased 22:6n-3 and the n-3/n-6 ratio in salmon and brown trout. By contrast, in charr fed the vegetable oil diet, there was no increase in 18:3n-3, 18:4n-3, 20:3n-3 or 20:4n-3 in liver polar lipid and the level of 22:6n-3 was not decreased. In addition, there was only a modest increase in the levels of 18:2n-6 and total n-6PUFA and so the n-3/n-6 ratio was only slightly decreased. The percentage of 20:4n-6, which was not increased in salmon and brown trout fed vegetable oil, was increased in charr fed the vegetable oil diet. Overall, ...